Transitional industrial designer – The responsibility of designers and companies for a sustainable transition - Michele Zannoni; Laura Succini; Ludovica Rosato; Veronica Pasini (Agathón)
In the current definition of sustainability, project cultures promote a transition involving changes in production, consumption and lifestyle, taking into account the progressive integration of environmental, social, cultural and economic aspects. By analysing eleven design approaches for sustainable, responsible, and circular transitions and, in particular, the disciplines of Advanced Design and Transition Design, this paper introduces the new figure of the Transitional Industrial Designer, a future-oriented designer with a critical awareness of the social and environmental implications of industrial design, able to contribute to more sustainable and adaptable models in a changing context. The article introduces the methods and tools tested in an EU-funded project.